GENETIC CHARACTERIZATION AND BARCODE CONSTRUCTION OF INDIGENOUS RICE VARIETIES AND ELITE LINES FOR INTELLECTUAL PROPERTY RIGHTS PROTECTION - MADIHA HABIB; Zaheer Abbas; Anila Latif; Muhammad Salman Mubarik; Amir Shehzad Naveed; Izhar Muhammad; Nafeesa Arjumand; Muhammad Rehan Naseem; Shaukat Ali; Ghulam Muhammad Ali; Jianlong Xu (Journal of Animal and Plant Sciences, 2025)
For the protection of farmers and consumer interests, rice varietal identification is a crucial part from a breeding point of view as well as seed production, and marketing. In this study, a total of 120 SSR primers extensively covering the whole rice genome were used to develop the varietal-specific DNA fingerprints of six indigenous rice varieties and nine elite rice lines. Among them, sixty-seven SSR primers were found polymorphic that amplified a total of 158 alleles. Diversity analysis of markers depicts the average number of amplified alleles (2.35), number of different alleles (Na: 0.534), effective alleles (Ne: 0.525), genetic diversity (0.375), observed heterozygosity (Ho: 0.120), expected heterozygosity (He: 0.062), fixation index (F: 0.936), Shannon’s diversity index (I: 0.089) and Polymorphic Information Content (PIC: 0.314). The phylogenetic tree, principal coordinate analysis (PCoA), and structure analysis grouped all the studied rice genotypes into two major categories that were subdivided into four subgroups depicting the underlying genetic variations. The amplified allelic pattern and size of twenty-four SSR primers were used to construct the varietal-specific barcodes, a digitalized representation of DNA fingerprints, that clearly and precisely showed genetic variation. The genotype-specific DNA fingerprints and the molecular marker information were used to generate the QR (quick response) barcode that can quickly scan through digital devices for rapid identification and management of varieties. These DNA fingerprints and barcodes of fifteen rice genotypes can ensure plant seed purity and can be used to protect intellectual property rights varieties.
Keywords: SSR; Rice; DNA fingerprint; Barcode; varietal identification; QR code